Seasonal Accumulated Workloads in Collegiate Men's Soccer: A Comparison of Starters and Reserves. Issue 11 (November 2021) - Curtis, Ryan M.; Huggins, Robert A.; Benjamin, Courteney L.; Sekiguchi, Yasuki; M. Arent, Shawn; C. Armwald, Bruin; Pullara, Jason M.; West, Chris A.; Casa, Douglas J.
Abstract : Abstract: Curtis, RM, Huggins, RA, Benjamin, CL, Sekiguchi, Y, Arent, S, Armwald, B, Pullara, JM, West, CA, and Casa, DJ. Seasonal accumulated workloads in collegiate men's soccer: a comparison of starters and reserves. J Strength Cond Res 35(11): 3184–3189, 2021—The purpose of this investigation was to quantify and compare player's season total-, match-, and training-accumulated workload by player status characteristics (i.e., starter vs. reserve) in American collegiate men's soccer. Global positioning system (GPS) and heart rate (HR)-derived workloads were analyzed from 82 collegiate male soccer athletes from 5 separate teams over the 2016 and 2017 seasons. Differences in total physical and physiological workloads (i.e., total distance, accelerations, and weighted HR-zone training impulse [TRIMP] score) as well as workloads over a range of intensity zones were examined using multilevel mixed models, with mean difference (MD) and effect size (ES) reported. Starters accumulated substantially more total distance (MD = 82 km, ES = 1.23), TRIMP (MD = 2, 210 au, ES = 0.63), and total accelerations (MD = 6, 324 n, ES = 0.66) over the season. Total accumulated distance in all velocity zones (ES [range] = 0.87–1.08), all accelerations zones (ES [range] = 0.54–0.74), and time spent at 70–90% HRmax (ES [range] = 0.60–1.12) was also greater for starters. Reserves accumulated substantially more total distance (MD = 20 km, ES = 0.43) and TRIMP (MD = 1, 683 au, ES = 0.79) during training. Although reserves show elevated physical and physiological loads during training compared with starters, there is an imbalance in overall workloads between player roles, with starters incurring substantially more match and total seasonal workloads. These results indicate managing player workloads in soccer requires attention to potential imbalances between players receiving variable match times. Coaches and practitioners in collegiate men's soccer may consider implementing strategies to reduce discrepancies in loading between starters and reserves. Individualized monitoring of training and match workloads may assist in the implementation of more balanced load management programs.